Climate smart agriculture: Concept and perspectives - Steliana Rodino; Alina Butu; Ana Maria Ifrim (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The negative effects of climate change are felt in the form of rising temperatures, weather variability, shifting boundaries of agro-ecosystems, the spread of invasive species and pests, and more frequent extreme weather events. Climate change reduces crop yields, the nutritional quality of most cereals, and lowers productivity in the livestock sector. In this regard, substantial investment in adaptation will be required to maintain current yields and to achieve increases in food production and quality to meet food needs under the expected exponential growth of the world's population.
Keywords: Q20; Q57; 330; climate change; agriculture; resilience; adaptation; CAP